Dynamics of land use and land cover in a Mexican national park - Pineda-López, Maria del Rosario; Ruelas Inzunza, Ernesto; Sánchez-Velásquez, Lázaro Rafael; Espinoza Guzmán, Marco A.; Rojo Alboreca, Alberto; Vásquez-Morales, Suria Gisela (Instituto de Ecología, A.C., 2017)
To understand the dynamics of land cover at the Parque Nacional Cofre de Perote, the rates of change in land use were compared at two different scales during the period 1995-2004. At the meso scale, these patterns were studied throughout the entire Parque Nacional Cofre de Perote, which is one of the 60 priority mountains of Mexico, and an important natural protected area of the country located in the state of Veracruz. At a micro scale, the work was focused in ejido El Conejo, located within the boundaries of this national park. Federal government digital orthophotos were used to determine changes in nine categories of land use. In both, the meso- and micro-scale, it was found that the predominant land cover categories are agriculture and forest. The probabilities of land cover change at both scales are low and essentially the same for most land use categories, reflecting both small gains in forest cover park-wide as well as the effectiveness of the ejido in managing natural resources within the park. The authors consider that the findings of the study may be applicable to the broader situation of national parks in Mexico and, finally, the importance of integrating local stakeholders in the management of natural protected areas is discussed.